Reducing the Rural-Urban Social Inequality: Chinese and Russian Comparative Experience - O. A. Antoncheva; T. E. Apanasenko (Управленческое консультирование)
Rural-urban social inequality in Russia is evident. Russian public opinion proposes to reduce the rural-urban income gap, both within the framework of the self-regulating market paradigm, reflected in public programmes, and within the planned command economy framework. In the same ways it proposes to achieve an inter-regional socio-economic balance.The People’s Republic of China (PRC) also faces the problem of reducing rural-urban social inequality. It looks as if it is trying to solve the problem by applying direct measures that can even reverse the processes of urbanization.This article proposes to analyze and adopt the most effective ways of reducing rural-urban inequality, as practiced in China. It is also possible to incorporate in the Chinese state’s management of social processes the methods of reduction of inequality between rural and urban populations, created by the dirigiste trends of Russian public thought, since the socio-economic system of the PRC readily assimilates elements of the planned economy.